Isolation-rearing from weaning to investigate depressive-like behaviour in the rat - Dunphy-Doherty, F. (2018)
Depression is a heterogeneous condition characterised by low mood and a lack of motivation and enjoyment of regular activities. The response rate to current treatments coupled with adverse side effect profiles requires new avenues of investigation into the development of novel therapeutics to treat the condition. Rearing rats in isolation from weaning causes behavioural, cognitive and neurochemical changes which persist into adulthood; some of the symptoms produced have relevance to depression. In the current thesis, rats raised in social isolation from weaning consistently developed a hyperactive phenotype compared to group-housed littermates when placed into a novel environment. They also developed deficits in associative learning assessed by the conditioned fear response task. They displayed some anxiety-like behaviours in the open field and novelty-suppressed feeding task and deficits in visual memory in the novel object discrimination task, although these were not reliable across cohorts. There was a reduction in levels of hippocampal neurogenesis in a number of cohorts and for the first time it was demonstrated that rats reared in isolation exhibited changes in gut bacteria, opening up a potential new avenue of investigation into potential treatments. The efficacy of novel versus established antidepressant treatments was evaluated in isolated rats. Chronic fluoxetine had some anxiolytic effects in the open field, attenuated isolation induced changes in associative memory and increased neurogenesis but also had inconsistent effects on activity. Treatment with acute ketamine increased freezing time in the conditioned freezing response task, indicating an improvement in associative memory. The final study examined, for the first time, the effect of treatment with the JNK-1 inhibitor DJNKI in isolation reared rats. DJNKI had some positive cognitive effects in both the novel object discrimination task and the conditioned freezing response task. In conclusion, the isolation rearing model induced varying levels of depression-like deficits, which were responsive to some treatments. The model is a useful tool for investigating the symptoms of depression and evaluating novel treatment options.